PROFIL PEMECAHAN MASALAH SISWA DALAM MEMECAHKAN MASALAH SPLDV BERDASARKAN TAHAPAN POLYA DITINJAU DARI GAYA KOGNITIF FI DAN FD - Suhatini, Percoyo Unggul; Trapsilasiwi, Dinawati; Yudianto, Erfan (Department of Mathematics Education , University of Jember, 2019)
This study aims to describe the profile of problem solving students based on the Polya stages in terms of cognitive style. The problem solving profile is a general description or description of the activities of solving mathematical problems carried out by students using previously acquired knowledge. The description is related to the psychological cognitive style possessed by students. Psychological cognitive style is divided into 2, namely the independent and field dependent cognitive style fields. Analysis of students' answers in the problem of the Two Variable Linear Equation System based on the 4 stages of the Polya consists of understanding the problem, making a plan of completion, implementing the completion plan and checking again. The instruments used were GEFT test, problem solving test, Two Variable Linear Equation System, and interview. The subjects of the study were 6 VIIIE class students at Genteng 2 Public Middle School. In general, field independent students are better at solving problems than field dependent students. Keywords: Cognitive Style, Problem Solving, Polya Stage, Profile.